2014
DOI: 10.1177/1687814020918097
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic brake characteristics of disc brake during emergency braking of the kilometer deep coal mine hoist

Abstract: Dynamic brake characteristics of disc brake during emergency braking of the kilometer deep coal mine hoist were investigated in the present study. The theoretical model of dynamic brake torque of disc brake during emergency braking was given to explore dynamic brake torque properties of disc brake. The three-dimensional thermo-mechanical coupled finite element model of brake disc–brake shoe was established to explore thermo-mechanical characteristics of disc brake during emergency braking. Effects of effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…The brake shoe has the density of 1788 g/cm 3 , an elastic modulus of 1031 MPa and Poisson's ratio of 0.23. The DSC differential scanning calorimeter is employed to measure the specific heat capacity of the brake shoe, and the evolution curve of specific heat capacity versus temperature is shown in Figure 1a.…”
Section: Performance Parameters Of the Brake Shoementioning
confidence: 99%
See 3 more Smart Citations
“…The brake shoe has the density of 1788 g/cm 3 , an elastic modulus of 1031 MPa and Poisson's ratio of 0.23. The DSC differential scanning calorimeter is employed to measure the specific heat capacity of the brake shoe, and the evolution curve of specific heat capacity versus temperature is shown in Figure 1a.…”
Section: Performance Parameters Of the Brake Shoementioning
confidence: 99%
“…Mining deep coal resources with a buried depth greater than 1500 m is a major development strategy in China. The hoisting mechanism for a 1.5-km-deep coal mine exhibits characteristics of large inertia and vibration as compared to that of a 1-km-deep coal mine [2][3][4]. When safety hazards, such as overspeed and the loss of control of the motor (when the motor continues to provide traction torque when it should be shut down at the end of hoisting), occur in the multi-rope friction hoist of a 1.5-km-deep coal mine [2], emergency braking between the brake disc and the brake shoe, with conditions involving high speed and high specific pressure and vibration [3,5,6], easily causes emergency braking tribological behaviors (uneven distributions of thermal stress and friction deterioration) of the brake shoe.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tests showed that the iron powder composites have the best effect. Da Gang Wang et al [7] studied dynamic characteristics of the brake of a kilometer mine hoist during emergency braking, the three-dimensional thermo mechanical coupling finite element model of disc brake shoe is established, and analyzed the influence of temperature field on emergency braking. Masoomi et al [8] proposed to use a friction material with thermal modulus to improve the braking performance of the hoist.…”
Section: Introductionmentioning
confidence: 99%